2017
DOI: 10.5194/acp-2017-1010
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Organic aerosol in the summertime Southeastern United States: Components and their link to volatility distribution, oxidation state and hygroscopicity

Abstract: 23The volatility distribution of the organic aerosol (OA) and its sources during the Southern 24Oxidant and Aerosol Study (SOAS; Centerville, Alabama) was constrained using 25 measurements from an Aerodyne High-Resolution Time-of-Flight Aerosol Mass 26Spectrometer (HR-ToF-AMS) and a thermodenuder. Positive Matrix Factorization (PMF) 27 analysis was applied on both the ambient and thermodenuded high resolution mass 28 spectra, leading to four factors: more oxidized oxygenated OA (MO-OOA), less oxidized 29 oxyge… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…However, Dall'Osto et al (2015) argued that the interpretation of the COA factor may be problematic as it may include OA from other 70 sources and not just cooking. Kostenidou et al (2018) also argued that the bbOA factor determined in the South US by Xu et al (2017) may include oxygenated OA from other sources. Yuan et al (2012) suggested that PMF factors may correspond to different stages of photochemical processing, rather than to independent sources.…”
Section: Introductionmentioning
confidence: 99%
“…However, Dall'Osto et al (2015) argued that the interpretation of the COA factor may be problematic as it may include OA from other 70 sources and not just cooking. Kostenidou et al (2018) also argued that the bbOA factor determined in the South US by Xu et al (2017) may include oxygenated OA from other sources. Yuan et al (2012) suggested that PMF factors may correspond to different stages of photochemical processing, rather than to independent sources.…”
Section: Introductionmentioning
confidence: 99%
“…The TD used in this campaign is a commercial product from ARI and has been applied widely in laboratory experiments (Saha et al, 2015;Huffman et al, 2009b;Grieshop et al, 2009b;Lee et al, 2011;May et al, 2013c;Saha and Grieshop, 2016;Sato et al, 2018;Champion et al, 2019 and reference therein) and field studies (Huffman et al, 2009a;Hu et al, 2016c;Paciga et al, 2016;Louvaris et al, 2017b;Cao et al, 2018;Kostenidou et al, 2018;Xu et al, 2021;Zhu et al, 2021 and reference therein). The TD consists of two parts: a heated section and a denuder section.…”
Section: Thermodenuder and Volatility Estimationmentioning
confidence: 99%
“…The volatility distribution of OA can be estimated based on either an empirical method (Faulhaber et al, 2009) or an evaporation kinetic model (Riipinen et al, 2010;Saha et al, 2015;Cappa, 2010a;Karnezi et al, 2014;Saha et al, 2017;Park et al, 2012;Epstein et al, 2009;Louvaris et al, 2017a). Based on the TD-AMS system, volatilities of ambient OA from urban/suburban (Xu et al, 2021;Louvaris et al, 2017b;Cao et al, 2018;Huffman et al, 2009a;Cappa and Jimenez, 2010;Saha et al, 2018;Paciga et al, 2016;Kang et al, 2022), rural (Zhu et al, 2021) and forest sites (Hu et al, 2016c;Saha et al, 2017;Kostenidou et al, 2018) have been explored. Huffman et al (2009a) first directly characterized chemically resolved volatility of ambient aerosols in urban areas, supporting the notion that OA components are semivolatile and primary organic aerosol (POA) is more volatile than secondary organic aerosol (SOA).…”
Section: Introductionmentioning
confidence: 99%
“…This differentiation was recommended in the peer review of Ulbrich et al (2009), due to the limitations of Pearson R for slowly varying time series concentrations. Similar to the seasonal PMF approach typically adopted, the time-of-day PMF approach does not account for uncertainties and time variations in relative ionization efficiencies of the detected species (Xu et al, 2018;Katz et al, 2021). Additionally, the sensitivity of the time-of-day PMF approach to the changing influence of outliers and the number of zeros has not been evaluated (Sect.…”
Section: Pmf (Me-2) Analysismentioning
confidence: 99%